New business models for research and development with affordability requirements are needed to achieve fair pricing of medicines. (13th January 2020) - Suleman, Fatima; Low, Marcus; Moon, Suerie; Morgan, Steven G
Abstract : For research and development to systematically deliver fairly priced medicines, new approaches to financing and organisation are needed, and affordability must be integrated into push, pull, and pooling mechanisms, say Fatima Suleman and colleagues